The reality of school book covers designs and ways to develop them (Journal of the College of Basic Education, 2022)
There is no country in the world that aspires to the progress of its people but has attached great importance to education, in order to be able to build an advanced and understanding generation that will lead the country to the highest stages of moral, scientific and cultural development, and we will be in the ranks of distinguished countries in various fields of life, and education is of the utmost importance related to the issue of human existence in Society, when the nation wants to advance its children towards progress and development, it must reform the educational system as one of the necessities of life.